Gross nitrogen mineralization and immobilization in temperate maize-soybean intercrops - Regehr, Alison; Oelbermann, Maren; Videla, Cecilia; Echarte, Laura (Springer, 2019)
Background and aims: Reliance on nitrogen (N) fertilizers to maintain crop productivity requires a thorough understanding of the transformation of this nutrient within the soil-plant system. Organic matter input from a mixture of crop residues, such intercrop systems, influence N transformations differently compared to sole crops. We tested the hypothesis that N mineralization and immobilization differ between cereal-legume intercrops and sole crops. Methods: A short-term experiment using 15N isotopic pool dilution was conducted in 2007 and 2012 in maize (Zea mays L.) and soybean (Glycine max L. Merr.) sole crops and 1:2 (1 row maize:2 rows soybean) and 2:3 (two rows maize:3 rows soybean) intercrops. Soil characteristics, gross mineralization and immobilization, and net immobilization to a 10 cm depth were quantified. Results: Soil characteristics (pH, bulk density, soil organic carbon (C), total N, and C:N) were not significantly different (P < 0.05) among treatments, but differed significantly (P < 0.05) between years (2007 vs. 2012). Soil NH4 +-N was significantly lower (P < 0.05) in the maize sole crop. Gross N mineralization, immobilization and net immobilization, were significantly different (P < 0.05) among treatments and between years. Relative NH4 +-N immobilization was significantly different (P < 0.05) among treatments and between years, showing the lowest values in the intercrops. The amount of NH4 +-N mineralized per day was significantly greater (P < 0.05) in the 2:3 intercrop and was significantly different (P < 0.05) between years in the 2:3 intercrop. Residence time of NH4 +-N was significantly longer (P < 0.05) in the soybean sole crop and 1:2 intercrop followed by the 2:3 intercrop and the maize sole crop. Conclusions: Intercropping contributed to the long-term immobilization of N and therefore was a more sustainable land-management practice than sole cropping. The adoption of cereal-legume intercrops will curb our currently growing reliance on N fertilizers.